The Relationship of Waste Sorting and Fly Density Levels in Temporary Shelter Places (TPS) In Madiun City - Vera C, Voti; Nur R, Karina; Widiarini, Retno (Syntax Corporation Indonesia, 2024)
Fly density can be a parameter for the success of waste management, both from containerization activities to final waste disposal, which must be integrated by sorting, collecting and transporting waste management. Waste that is not sorted can cause problems, one of which is disease caused by vectors. In this research, researchers used quantitative research as an approach. The research method used is an analytical survey while the type of research is cross sectional. The total population is 36 polling stations with a sample size of 20 polling stations using the Chi-Square test. Research shows that the independent variable value of sorting is significant (p-value = 0.014), with the level of fly density in the Madiun City Temporary Shelter (TPS). There is a relationship between waste sorting and the level of fly density in the Madiun City Temporary Shelter (TPS).